h(t) = t - 1
f(t) = -t - 1
g(t) = |t|
-Compute the multipart rules for g(h(t)) and h(g(t)) and sketch their graphs
So what I did first was mainly subsitution since we got the values
So for g(h(t)) would be:
g(h(t)) = g(t-1)
g(t) = |t|
g(t-1) = |t-1|
h(f(t)) = t-1 if __________
-t + 1 if _________
How do you get the 'if part'
in the answer book, it's 1<t for t-1
and t<1 for -t+1
f(t) = -t - 1
g(t) = |t|
-Compute the multipart rules for g(h(t)) and h(g(t)) and sketch their graphs
So what I did first was mainly subsitution since we got the values
So for g(h(t)) would be:
g(h(t)) = g(t-1)
g(t) = |t|
g(t-1) = |t-1|
h(f(t)) = t-1 if __________
-t + 1 if _________
How do you get the 'if part'
in the answer book, it's 1<t for t-1
and t<1 for -t+1
Last edited: